2017
DOI: 10.1186/s12870-017-1025-3
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediate tapetal programmed cell death in tobacco and tomato

Abstract: BackgroundHybrid vigor is highly valued in the agricultural industry. Male sterility is an important trait for crop breeding. Pollen development is under strict control of both gametophytic and sporophytic factors, and defects in this process can result in male sterility. Both in the dicot Arabidopsis and in the moncot rice, proper timing of programmed cell death (PCD) in the tapetum ensures pollen development. Dynamic ROS levels have been reported to control tapetal PCD, and thus pollen development, in Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…The anthers were then collected in the tetrad stage, early uninucleate stage, late uninucleate stage, binucleate stage, and trinucleate stage. The total DNA was isolated from the DPI-treated anthers in different developmental stages and subjected to DNA laddering analysis ( Yu et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The anthers were then collected in the tetrad stage, early uninucleate stage, late uninucleate stage, binucleate stage, and trinucleate stage. The total DNA was isolated from the DPI-treated anthers in different developmental stages and subjected to DNA laddering analysis ( Yu et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Biosynthesis of NO is catalyzed by nitrate reductase (NR), a well-known route of reductive reactions, and nitric oxide synthesis (NOS)-like biochemical pathway [ 25 , 26 ]. Previously, there are more evidence showed that NO could modulate ROS generation, which is always accompanied by oxidative stress, to keep redox homeostasis and decrease oxidative damage [ 18 , 27 ]. Specific plant proteins involved in metabolism, stress responses, and redox homeostasis, have also been identified as possible targets for S -nitrosylation, one of NO-dependent post-translational modifications [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROS are important signalling molecules necessary for multiple biological processes (Mittler, ) and play a key role in tapetal PCD (Yu et al, ). Failure to remove the excessively accumulated ROS in the tapetum would result in male sterility by causing precocious tapetal PCD (Hu et al, ; Luo et al, ; Xie et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The timely initiation of tapetal PCD during microspore development is found to be largely affected by dynamic changes of the endogenous level of reactive oxygen species (ROS; Hu et al, ; Ko et al, ; Xie, Wan, Li, & Zhang, ; Yu, Feng, Xie, Li, & Zhang, ), which are key signalling molecules involved in various biological processes and stress responses (Mittler, ). Relevant researches have unveiled that the cellular ROS level is very sensitive to temperature changes, and maintaining ROS homeostasis associates intimately with the adaptation to extreme temperature in rice (Baxter, Mittler, & Suzuki, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%